PENGARUH PROFITABILITAS, LIKUIDITAS, GROSS REVENUE DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN REAL ESTATE AND PROPERTY YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2019-2022 - Tandyono, Jessica; Lilia, Wirda; Anita, Anita; Novirsari, Emma (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
In its business activities, companies aim to increase their value in each period. Companies have short-term and long-term goals. In the short term, companies aim to maximize profits, while their long-term goal is to increase their value. The purpose of this study is to examine the influence of profitability, liquidity, gross revenue, and company size on the value of companies listed on the Indonesia Stock Exchange for the 2019-2022 period. This study was conducted in real estate and property companies listed on the Indonesia Stock Exchange for the 2019-2022 period. The sample size used in this study was 76. The partial results of the study indicate that Return on Assets has a positive and significant effect on Price to Book Value, Current Ratio has a negative and insignificant effect on Price to Book Value, Gross Revenue has a positive and significant effect on Price to Book Value, and Size has no significant effect on Price to Book Value. Simultaneously, Return on Assets, Current Ratio, Gross Revenue and Size have a positive and significant influence on Price to Book Value.